How to measure hedonic property price indexes better - Mick S. Silver (Eurostat Review on National Accounts and Macroeconomic Indicators (EURONA), 2018)
Hedonic regressions are used for residential property price index (RPPI) measurement to control for changes in the quality-mix of properties transacted. This paper consolidates the confusing array of existing approaches and methods of implementation. It further develops an innovative form of weighting at the (elementary) level of the individual property and, therefrom, quasi-superlative and superlative formulations that improve on those in the literature. Well-grounded, practical, quasi-superlative RPPIs with dual imputations are devised that are suitable for thin markets and sparse data and not subject to the vagaries of the periodic estimation of hedonic regressions. All of this is with no additional data requirements and suitable for real time production.
Keywords: C43; E30; E31; R31; 330; hedonic regressions; residential property price index; commercial property price index; house price index; superlative index number formula